Minimally Invasive Reduction and Stabilization of Fractures of the Humeral Condyle by Skeletal Traction in Dogs: 18 Cases - Benedini, Davide; Rovesti, Gian Luca; Barbieri, Fabio (VCOT Open, 2022)
Closed reduction or limited open reduction in conjunction with internal or external fixation has been recommended as the preferred treatment for many types of fractures, but this technique has rarely been recommended for articular fractures because of the need for anatomic alignment of articular surfaces. However, the proposed benefits of closed reduction should be applicable to articular fractures if appropriate reduction and implant placement can be achieved. The aim of this study was to retrospectively evaluate a surgical technique for minimally invasive reduction and stabilization of fractures of the humeral condyle by means of intraoperative traction applied to the ulna under fluoroscopic guidance. Nineteen fractures of the humeral condyle in eighteen dogs were reduced by intraoperative osteotaxis applied by traction of the ulna, minimally invasive approach to the epicondyle and fracture stabilization under fluoroscopic guidance. Postoperative reduction was considered good or excellent in most fractures. This technique can be considered as a potential option for the treatment of condylar fractures, allowing for minimally invasive reduction and stabilization, thus avoiding the need for surgical exposure of the elbow joint.
Keywords: fracture of the humeral condyle; minimally invasive stabilization; skeletal traction; dogs